The defect and dielectric properties of Nb and Mn co-doping BaTiO3 ceramics. (10th September 2018) - Yang, Xiaojing; Liu, Xiaobing; Ding, Shihua
Abstract: The effect of Nb and Mn as dopants on the dielectric properties of BaTiO3 based ceramics was investigated. When the content of Nb <1.0% mol (Mn =1.6% mol), a diffuse phase transition (DFT) character appeared, and a normal-like ferroelectrics character was observed as the content of Nb is 1.0% mol. When the content of Nb increases up to 1.1% mol, it showed a dielectric relaxation. The binding energy for different defect associations [2 N b T i + V B a ″ ] and [V O + 2 M n T i ′ ] calculated using computer simulation techniques and the dielectric properties related to polar nanoregions (PNRs) were discussed.